Effect of phosphorus fertilisation on growth, yield and quality of pea (Pisum sativum) - JAKIR HUSAIN; POONAM KASHYAP; A K PRUSTY; DEBASHIS DUTTA; SHIV SHANKAR SHARMA; A S PANWAR; SUNIL KUMAR (The Indian Journal of Agricultural Sciences, 2019)
In the present study, experiments were undertaken during 2016-2017 to examine the effect of phosphorus application on pea (Pisum sativum L.) cv. Arkel and Azad P-1. Four levels of phosphorus (0, 60, 90, 120 kg/ha) keeping the N at K dose constant at 25 and 50 kg ha-1 respectively with 3 replications were used in two way factorial analysis. The effects of different doses of phosphorus were judged on growth, yield and quality attributes. Evaluation of comparative performance of pea varieties Arkel and Azad P-1 in the climatic condition of Western plain zones of Uttar Pradesh suggested better performance of Azad P-1 over Arkel. However, on studying the interaction between NPK levels and Variety, Azad P-1 with P @ 120 kg ha-1 registered maximum pod yield (9.24 kg/plant) than Arkel (8.55 kg/plant). Results revealed that the performance of pea variety Azad P-1 was better than the variety Arkel. The higher number of pods per plant (17.94), weight of pods per plant (124.86 g), number of grains per pod (7.72) and pod yield per plot (7.79 kg) was recorded in the variety Arkel than Azad P-1. The study also revealed that ascorbic acid as well as total sugar content in harvested pods showed a declining trend with higher level of phosphorus irrespective of variety. Thus, pea variety Azad P-1 was found to be performing better with phosphorus application of 120 kg/ha in terms of growth, yield and quality attributes. This variety can hence be recommended for integration in horticulture based farming systems of Western Uttar Pradesh.